Zinc Oxide Nanoparticles as Diagnostic Tool for Cancer Cells - Ibraheem, Sumayah; Kadhim, Afraa Ali; Kadhim, Kadhim Ali; Kadhim, Ihssan A.; Jabir, Majid (International Journal of Biomaterials, 2022)
ZnO nanoparticles have various characteristics that make them attractive to be used in many medical applications like a cancer diagnosis. It can be used as a nanoprobe for targeting different types of cancer cells in vitro as a cancer cell recognition system. The present study aims to investigate the permeability of ZnO NPs through both normal and cancerous cell lines in humans. In vitro experiments for ZnO NPs inside the environment of living cells have been described, which would contribute to the visualization of nanoparticles as cancer diagnostic and scanning techniques. MCF7, AMJ13, and RD cancer cells, and also the normal breast cell line HBL, were used in in vitro imaging experiments. The findings revealed that ZnO NPs specifically incorporated within tumor cells while accumulating less inside normal cells. Our findings show that ZnO NPs may be identified inside cancer cells after 1 h of exposure and can endure up to 3 h, providing them appropriate for tumor cell imaging. The findings showed that ZnO NPs might be employed as an alternate fluorophore for diagnostic imaging in the early identification of solid cancers. Therefore, here we studied in vitro applications of ZnO NPs and their beneficial use as a diagnostic tool for cancer cell lines rather than normal cells. Taken together, ZnO NPs can be used as good targeting NPs for the development of imaging agents for early diagnosis of cancers.